Technique for conducting experimental studies on stress-strain state of P-3 profile interference fits - Elena A Rozhkova (RUDN Journal of Engineering Researches, 2018)
In mechanical engineering the following profile connections are applied most often: with three sides (P-3); with three cut off sides (PC-3); with four cut off sides (PC-4) and with five sides (P-5 and PC-5). Despite considerable results, in the field of studying of stresses and deformations at contact interaction of solid bodies of various forms there is an unresolved number of tasks, which are of scientific and practical value. As the analysis of theoretical and experimental studies of motionless detachable and non-detachable connections (cylindrical, profile) has shown, there are unresolved tasks, in particular regarding the choice of geometrical form of contour curves, the magnitude of interference fit of motionless, non-detachable profile connections with equiaxial contour. The working capacity and reliability polygon profile connections with interference fit is defined by their strength, that is ability of elements to resist strain when in use. For the purpose of determination of working capacity of polygon profile connections with interference fit with respect to strength, stresses and deformations arising in hub with polygon profile opening from the action of polygon profile shaft installed in a nave with interference fit. The article considers the technique of conducting experimental studies by strain-gauging method for the purpose of assessing the influence of structural parameters and external loadings on stress-strain state of parts of the connection. Based on the experimental results tables of comparative characteristics of the recommended types of interference fits for P-3 profile connections and also the recommended interference fits for the corresponding n values of P-3 profile shaft-nave connections applied for tooth gearings were composed.